Analisis Kepuasan Pengguna Website Zahira Media Publisher Menggunakan Metode End User Computing Satisfaction (EUCS) - Adinda Arininta Loysiana; Shafni Nur Hikma; Falia Nur Afifah; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze user satisfaction with the website of Zahira Media Publisher, a publishing company that has been operating since 2012. Using a descriptive analysis method and a quantitative approach, this study collected data through a questionnaire designed based on the End User Computing Satisfaction (EUCS) model. The five main variables analyzed include content, accuracy, format, ease of use, and timeliness of information. The results showed that the quality of content and the accuracy of information greatly influenced user satisfaction. In addition, the ease of use of the website is also an important factor that improves user experience. that improves user experience. Although the Zahira Media Publisher website offers a wide range of publishing services, there are some obstacles, especially in the process of registering new user accounts, which can hinder access to key features. This research provides recommendations for improvements in website design and functionality to increase user satisfaction and customer loyalty.